Microbiological examination of column water in Terengganu (kualiti mikrobiologi turus air di Terengganu, Malaysia) - Rahman, Md. Mokhlesur; ., Nazroon; Wan Nik, Wan Norsani (Malaysian Society of Analytical Sciences (ANALIS), UKM, 2009)
The microbiological quality of rural column water at Terengganu was determined. Coliform (E.coli), algae, fungi and total count of bacteria were used indicators for the hygienic quality of the Kuala Terengganu water. Membrane filter method and direct count method were applied for the purpose of detection and enumeration. Conclusions relative to the water quality status, as well as the possible reasons for water quality problems are presented in this paper. Obtained results indicated that the water quality status of Kuala Terengganu area cannot cope up with the Malaysia Ministry of Health or World Health Organization standards. Generally the water quality depends on its microbiological conditions. On the other hand, the presence of the micro-organisms in some column water showed that some of the ground water Kuala Terengganu is polluted.